Corrosion Resistance of TIG Welding Joint for Aluminium Alloy 6061- T6 in Sea Water at Different Velocities - Abdul rahim Khudadad, Mussa; Nife Frhan, Entsar (Journal of Engineering and Sustainable Development, 2014)
An experimental investigation has been carried out on the microstructure, microhardness distribution, and corrosion behavior of weld butt joints of 6061 T6 aluminum alloy. Arc welding processes by tungsten inert gas (TIG) have been carried out on a Rolled sheets of 4mm thickness to obtain many welding joints with dimensions of (100 *50* 4)mm using ER4030 (Al Si5 ) as filler metal and argon as shielding gas. The other parameters were: welding current 180 amperes, voltage 20 volts, filler rod diameter 1.2 mm, welding speed120 mm/min, gas flow 20 L/min and two passes of the weld All welded pieces were tested by X-ray radiography and faulty pieces were excluded. The joints without defects were used to prepare many specimens for corrosion tests by the dimensions of (15*15*3) mm according to ASTM G71-31 then Optical microscopy was used to observe the welded joint microstructure. The corrosion test was implemented by using potential static polarization measurements in seawater 3.5%NaCl at a temperature of 25°C, and different velocities (1, 2, and 3) m/min. The potential of the circuit was determined by an open circuit depending on AL in electrochemical series after that the rate of the cell’s current is changed due to 100± (m v). The obtained results by the Tafel equation show that velocity contributed to increasing the corrosion resistance of 6061 T6 Al alloy for all specimens and TIG weld joints give low corrosion rates than the base metal because of changes in microstructure in the weld zone.